Taming the Jungle in the City: Uprooting Trees, Bushes, and Disorder from Mount Royal Park - Caron, Matthieu (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2018)
From the late 1940s to the early 1960s, Montreal’s obsession with regulating immoral behaviour led to several urban renewal schemes. This article looks at the municipal government’s decision to clear an overgrown section of Mount Royal Park nicknamed the “Jungle” and ultimately to reconstruct it as a heterosexual space. This area of the park was highly patrolled by police officers who viewed it as a gathering place for undesirable persons; newspapers highlighted how drunkards, criminals, sex maniacs, perverts, and, most importantly, homosexuals defiled the park’s character. To rid Mount Royal Park of its Jungle and those who had appropriated it, the city came up with a radical plan to simplify the police department’s techniques of surveillance: the ecological clearance of the Jungle. The clearcutting of the Jungle, a process known as the Morality Cuts, eroded the environmental and ecological character of Mount Royal, with the immediate repercussion of “balding” the park. However, in the aftermath, the mobilization of other civic actors, including civil servants and the Montreal Parks and Playgrounds Association, enabled a restorative strategy for the park’s ecology.